Serum estradiol (E2), progesterone (P), and human chorionic gonadotropin (HCG), D-dimer (D-D) fibrinogen (FIB) levels after Low Molecular Weight Heparin Sodium on Preventing Miscarriage in Patients with Adverse Pregnancy and Delivery: Serum E2, P, HCG, D-dimer , fibrinogen in Adverse Pregnancy - Pei, Liucheng (Journal of Medical Biochemistry, 2025)
Introduction: It was to investigate the effect of subcutaneous injection of low molecular weight heparin (LMWH) sodium on preventing miscarriage in patients with adverse pregnancy and childbirth and on Serum estradiol (E2), progesterone (P), and human chorionic gonadotropin (HCG), D-dimer (D-D) fibrinogen (FIB) levels. Material and Method: Eighty-two patients with adverse pregnancy admitted to Wuhai Maternal and Child Health Hospital from April 2024 to December 2024 were randomly grouped, 41 cases in each group. Controlgroup(CG) adopted dydrogesterone, and observation group (OG) adopted subcutaneous injection of LMWH sodium on this basis. The sex hormones, pre-thrombotic state (PTS) indexes, and application effects were compared between two groups before and after treatment. Result: progesterone (P), Estradiol (E2), and human chorionic gonadotropin (HCG) in OG were higher as against CG (P<0.05). APTT, prothrombin time (PT), thrombin time (TT), and plasminogen (PLG) in OG were higher as against CG. The levels of fibrinogen (FIB) and D-dimer (D-D) were inferiorin OG as against CG (P<0.05).In terms of thromboelastogram (TEG) parameters, patients in the OG exhibited higher R and K values versusCG, while MA, Angle, and CI values were lower than those in the CG (P<0.05).The total response rate of OG (95.12%) was higher as against CG (75.61%) (P<0.05). The cases of neonatal malformation, low body weight, and death in OG were lower as against CG, and the differences in the cases of neonatal malformation and low body weight were obvious (P<0.05). Conclusion: Subcutaneous injection of LMWH sodium can help improve sexhormone levels and reduce PTS in patients with adverse pregnancy and childbirth, with good application effects